Pendampingan Pembuatan Laporan Keuangan Pada Usaha Dagang Ud. Palwa Group - Hasbullah Hasbullah; Dewi Silvia; Amelia Anwar; Moli Perani; Eva Desriantika (Universitas Maritim AMNI Semarang, 2023)
Community service activities to provide knowledge about assisting in the preparation of financial reports at UD. Palwa group. This activity was carried out on May 4 2023 to May 11 2023. The method of activity is by presenting material, discussions, training and mentoring. a series of community service activities as follows: the implementing team presents material on preparing financial reports, the practice of making financial reports manually and digitally, solicits participant feedback regarding the quality of the training including material understanding, activity benefits and activity implementation satisfaction.